问题
解答题
|
答案
(1)36×
,17 35
=(35+1)×
,17 35
=35×
+1×17 35
,17 35
=17+
,17 35
=17
;17 35
(2)
×4 5
+2 3
÷1 5
,3 4
=
×4 5
+2 3
×1 5
,4 3
=
×4 5
+2 3
×4 5
,1 3
=
×(4 5
+2 3
),1 3
=
×1,4 5
=
;4 5
(3)
×(12 5
+5 6
)+3 4
,4 5
=
×12 5
+5 6
×12 5
+3 4
,4 5
=2+
+9 5
,4 5
=2+(
+9 5
),4 5
=2+2
,3 5
=4
;3 5
(4)(
+4 9
)÷2 15
,2 15
=(
+4 9
)×2 15
,15 2
=
×4 9
+15 2
×2 15
,15 2
=
+1,10 3
=4
;1 3
(5)
÷3+1 5
×4 5
,1 3
=
×1 5
+1 3
×4 5
,1 3
=(
+1 5
)×4 5
,1 3
=1×
,1 3
=
;1 3
(6)13
-(47 13
+31 4
),7 13
=13
-47 13
-31 4
,7 13
=13
-37 13
-47 13
,1 4
=10-4
,1 4
=5
.3 4